تقويم برنامج تفاعلي في تعليم التعبيرات الاصطلاحية في اللغة العربية لدى الدارسين الناطقين بغيرها باستخدام برنامج الوسائط المتعددة - Amani Binti Nawi; Mohd Sabri Shahrir (Al-Quds Open University, 2024)
The purpose of this study is to help learners of Arabic to learn Arabic idiomatic expression by designing a prototype courseware for them to learn these idioms and to investigate the difficulties experienced by the learners in identifying and understanding them. Previous studies have listed numerous reasons for the difficulties experienced by the non- native Arabic learners in acquiring reading skills. One of the reasons is the inability to identify and understand the Idiomatic expression in Arabic. This study uses systematic, descriptive and analytical methodologies, where the descriptive approach was adopted to facilitate the gathering of information about Arabic idioms and theories of learning through multimedia. On the other hand, there were three stages of scientific procedures in analytical approach. Firstly, learners need analysis which was completed before the phase of design. Secondly, experts review analysis which was conducted during the design phase. The third stage was the analysis of formative evaluation by the learners after the completion of the development phase. The participants of this study were 40 students who are learning the subject of computer application in Arabic language and literature (ARAB 2124) and they were selected to participate in the evaluation phase. The prototype courseware implemented the theory of learning by Mayer and ADDIE model in its design and development by using PowerPoint, ISpring, and Adobe Flash. The result of this study showed that students cannot identify Arabic idiomatic expression and understand their meanings due to their lack of reading Arabic books. These idioms have not been taught in any particular subject or textbook, thus, students are unaware of their importance and could not use them.